Aktivitas Analgesik Ekstrak N-Heksana Daun Marsilea crenata Presl. dengan Metode Geliat pada Mencit - Fathia Faza Rahmadanita; Mangestuti Agil; Neny Purwitasari (Journal of Islamic Pharmacy, 2021)
The objective of this study was to evaluate the analgesic activity of n-hexane extract of Marsilea crenata Presl. The analgesic effect was examined by acetic-acid-induced writhing response. Before intraperitoneally injection of acetic acid 0,6%, drugs were orally administered to Balb/C mice. This animal divided into 5 groups, positive control (Ibuprofen 1,04 mg/20 g BW mice), negative control (10% tween 80), dose 1 (0,27 mg/20 g BW mice), dose 2 (0,54 mg/20 g BW mice), and dose 3 (0,81/20 g BW mice). The number of writhings exhibited by each animal was counted for thirty minute beginning five minute after acetic acid induction. Obtained data were analyzed by one-way ANOVA followed by LSD test with confident level was 0,05. Dose 1, dose 2, and dose 3 showed significant different to negative control (p0,05). Dose 1 (0,27 mg/20 g BW mice) almost equal to positive control (p0,05). This study indicate that n-hexane extract of Marsilea crenata has analgesic effect. The obtained results provide information for the potential use in the treatment of pain